Brilliant Minds: A Snapshot of Successful Indigenous Australian Doctoral Students. Issue 1 (11th May 2016) - Trudgett, Michelle; Page, Susan; Harrison, Neil
Abstract : Drawing on demographic data collected from interviews with 50 Indigenous Australians with a doctoral qualification and 33 of their supervisors, this paper provides the first detailed picture of Indigenous doctoral education in Australia, with the focus on study modes, age of candidates, completion times and employment. It also analyses data produced through interviews with supervisors including age, employment levels and academic background. The study confronts a number of common perceptions in the higher education sector, to find that many Indigenous Australians are awarded their doctoral qualification in the middle stages of their career. This particular cohort is more likely to be studying in the arts and humanities, employed in higher education and enrolled on a full-time basis. This Australian Research Council (ARC) funded research provides new and important data to inform government policy, and to allow universities to implement strategies and recommendations arising from the Behrendt Report of 2012.